2023
DOI: 10.3324/haematol.2022.281653
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive molecular and clinical characterization of <i>NUP98</i> fusions in pediatric acute myeloid leukemia

Abstract: NUP98 fusions c omprise a family o f rare r ecurrent a lterations i n A ML, associated w ith adverse outcomes. To define the underlying biology and clinical implications of this family of fusions, we performed comprehensive transcriptome, epigenome, and immunophenotypic profiling of 2,235 children and young adults with AML and identified 160 NUP98 rearrangements (7.2%), including 108 NUP98-NSD1 (4.8%), 32 NUP98-KDM5A (1.4%) and 20 NUP98-X cases (0.9%) with 13 different fusion partners. Fusion partners defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Bertrums et al recently identified 13 different fusion partners for NUP98 via transcriptome analysis in a cohort of 2235 children suffering from pediatric AML [45]. In total, at least 39 different fusion partners have been described to date, which can be subdivided into homeodomain (HD)-containing genes (at least 11 partners) and non-HD genes (at least 28 partners) [4,22,[45][46][47][48]. Intriguingly, ASH1L has not been detected as a fusion partner for NUP98 so far.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bertrums et al recently identified 13 different fusion partners for NUP98 via transcriptome analysis in a cohort of 2235 children suffering from pediatric AML [45]. In total, at least 39 different fusion partners have been described to date, which can be subdivided into homeodomain (HD)-containing genes (at least 11 partners) and non-HD genes (at least 28 partners) [4,22,[45][46][47][48]. Intriguingly, ASH1L has not been detected as a fusion partner for NUP98 so far.…”
Section: Discussionmentioning
confidence: 99%
“…Of all 35 fusion partners mentioned in a review published in 2020 by Michmerhuizen et al, only the rare NUP98-fusions ::IQCG, ::RARG, and ::MLLT10 had DNA strand orientations that required a more complex genomic rearrangement than a single translocation or inversion, as shown for the novel NUP98::ASH1L [4, [77][78][79]. Two other exceptionally rare NUP98-fusions, namely ::BRWD3 and ::TAF3, also fell in this category [45][46][47]. The necessity of a more complex rearrangement in these cases with more than two chromosomal breakpoints might partially explain why NUP98::ASH1L has not been described before.…”
Section: Nup98::ash1l In Context Of Nup98-rearrangementsmentioning
confidence: 96%
See 1 more Smart Citation
“…It should be mentioned that NUP98::ASNSP4 as an unreported new fusion was just identified in a B-ALL patient (Table S1). It should also be mentioned that the partner gene of NUP98 in de novo AML was NSD1 (24), HOXA9 (9), PRRX2 (3), HMGB3 (2) and others (7), whereas in t-AML were NSD1 (1), HOXA9 (1) and TOP1 (1), and in s-AML were PRRX2 (1), KDM5A (1) and DDX10 (1) individually.…”
Section: Dear Editormentioning
confidence: 99%
“…The NUP98 gene is rearranged with approximately 30 partners in AML (Table 1). NUP98::NSD1 and NUP98::KDM5A are frequently occurring NUP98 fusions in AML [30]. NUP98 gene alterations have been implicated in several hematological malignancies including AML, chronic myeloid leukemia (CML), juvenile myelomonocytic leukemia (JMML), T-cell acute lymphoblastic leukemia (T-ALL), and myelodysplastic syndrome (MDS) [26].…”
Section: Fusion Partners Of Nup98 In Nup98-rearranged Amlmentioning
confidence: 99%